FISIC-QUIMICS PARAMETERS OF BRAZILIAN OLIVE OIL FIRST EXTRACTED IN MARIA DA FÉ CITY, MINAS GERAIS - OLIVEIRA, Adelson Francisco de; VIEIRA NETO, João; GONÇALVES, Emerson Dias; VILLA, Fabíola; SILVA, Luiz Fernando de Oliveira da (Scientia Agraria, 2010)
The present work had for objectives to verify the characteristics physicist-chemistries of different olive varieties introduced in the Maria da Fé city, south of Minas Gerais, Brazil, with the purpose to select those adjusted for olive oil extration. Olive oil was extracted from fruits of seven olive cultivars in 2007/2008 harvest. Size and weight in fruit and acidity, peroxide value, iodine value, absolute refractive value at +20 °C, ultraviolet absorbance at 270 nm and 232 nm and fatty acids profile by gas chromatography in olive oil were evaluated. The data were compared with results obtained from two olive oil commercial samples and with parameters set by Codex Alimentarius. The first olive oil extracted from fruit of seven cultivars was previously classified as extra virgin. In all the olive oil analyzed was observed in oleic acid content above 64.39%, with higher concentrations in cultivars Penafiel SP and Alto D’Ouro, according to Brazilian legislation.